Structure for architects : a primer - Dabby, Ramsey; Bedi, Ashwani (Wiley, 2012)
"Structure for Architects explains the fundamental structural concepts required for architects and architectural technologists using a highly illustrated approach and real-world examples. With an intuitive, easy-to-read and graphically-friendly format, Structure for Architects is meant for the visual thinker and those that think conceptually. The intuitive approach demystifies structural principles by showing them in the context of everyday situations. Eschewing complicated mathematics, just enough technical information is presented so the reader will not be intimidated by detailed engineering"